2005
DOI: 10.1042/bj20040933
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic farnesyl diphosphate synthase expression is suppressed by polyunsaturated fatty acids

Abstract: Dietary vegetable oils and fish oils rich in PUFA (polyunsaturated fatty acids) exert hypocholesterolaemic and hypotriglyceridaemic effects in rodents. The plasma cholesterol-lowering properties of PUFA are due partly to a diminution of cholesterol synthesis and of the activity of the rate-limiting enzyme HMG-CoA reductase (3-hydroxy-3-methylglutaryl-CoA reductase). To better understand the mechanisms involved, we examined how tuna fish oil and individual n-3 and n-6 PUFA affect the expression of hepatic FPP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 50 publications
4
38
0
3
Order By: Relevance
“…Our trial to identify key molecules in the EPA function on SREBP-2 processing has been unsuccessful so far, which leads us to reconsider roles of EPA. At present, a likely hypothesis is that EPA may modify membrane fluidity, which could be followed by enrichment in cholesterol in order to preserve membrane stability, as described by Le Jossic-Corcos et al (2005). The change in membrane fluidity could inhibit escorting the SREBP cleavage activating protein-SREBP-2 complex from endoplasmic reticulum to the Golgi apparatus, where the proteolytic processing occurs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our trial to identify key molecules in the EPA function on SREBP-2 processing has been unsuccessful so far, which leads us to reconsider roles of EPA. At present, a likely hypothesis is that EPA may modify membrane fluidity, which could be followed by enrichment in cholesterol in order to preserve membrane stability, as described by Le Jossic-Corcos et al (2005). The change in membrane fluidity could inhibit escorting the SREBP cleavage activating protein-SREBP-2 complex from endoplasmic reticulum to the Golgi apparatus, where the proteolytic processing occurs.…”
Section: Discussionmentioning
confidence: 93%
“…The mechanisms of their lipid-lowering effects have been tentatively established (Field et al, 2002;Yoshikawa et al, 2002;Davidson, 2006). EPA is currently used as a hypolipidemic drug, ethyl all-cis-5,8,11,14,17-icosapentaenoate, and is demonstrated to modulate gene expression in lipid and glucose homeostasis (Jump et al, 1994;Field et al, 2002;Le Jossic-Corcos et al, 2005). The hypotriglycemic effect of EPA mainly results from the combined effects of the inhibition of lypogenesis, and the stimulation of fatty acid oxidation in liver (Ren et al, 1997;Yahagi et al, 1999;Clarke, 2001;Jump et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…SREBP also regulates the transcription of cholesterol synthesis enzymes, such as 3-hydroxy-3-methylglutarylCoA reductase HMG-CoA reductase , the rate-limiting enzyme. N-3 PUFA is known to improve cholesterol and lipoprotein metabolism 41,42 , and its hypocholesterolemic effect is mainly due to suppression of HMG-CoA reductase at the transcriptional level 43,44 . Le Jossic-Corcos and others showed that EPA and DHA exhibit inhibitory effects on cholesterol production through reduction of these genes in human hepatoma HepG2 cells, and suggested that such negative effects occur as a result of downregulation of SREBP gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The ω3-PUFAs have been shown to increase plasma LDL with large particle size, which is much less atherogenic than LDL that cannot infiltrate blood vessels of vascular endothelium to start development of atherosclerosis [24]. Moreover, ω3-PUFAs downregulate sterol regulatory element-binding protein, resulting in suppression of gene expression of 3-hydroxy-3-methyl-glutaryl CoA reductase, a rate-limiting enzyme in cholesterol synthesis [25]. ω3-PUFAs also activate liver X receptors that upregulate expression of 7-α-hydroxylase, the main enzyme in conversion of cholesterol into bile acids [26].…”
Section: Healthy Fatsmentioning
confidence: 99%